IMPRISONMENT LENGTH AND POST‐PRISON EMPLOYMENT PROSPECTS1. Issue 3 (27th June 2014) - RAMAKERS, ANKE; APEL, ROBERT; NIEUWBEERTA, PAUL; DIRKZWAGER, ANJA; VAN WILSEM, JOHAN
<x xml:space="preserve">Abstract</x> This study considers the relationship between imprisonment length and employment outcomes. The data are a unique prospective, longitudinal study of Dutch pretrial detainees (N = 702). All subjects thus experience prison confinement of varying lengths, although the durations are relatively short (mean = 3.8 months; median = 3.1 months). This contrasts with prior research that was limited to the study of American prison sentences spanning an average of 2 years. These data thus fill a gap in the empirical base concerning short‐term confinement, which is the norm in the United States (e.g., jail incarceration) and other Western countries. Using a comprehensive array of pre‐prison covariates, a propensity score methodology is used to examine the dose–response relationship between imprisonment length and a variety of employment outcomes. The results indicate that, among prison lengths less than 6 months in duration, longer confinement is largely uncorrelated with employment. In contrast, among spells in excess of 6 months, longer imprisonment length seems to worsen employment prospects.